TOPIK BALANCE SCORECARD DALAM LITERATUR AKUNTANSI DI INDONESIA: STUDI BIBLIOGRAFI - Maya Aulia Saputri (Jurnal Akuntansi Trisakti, 2021)
This study aims to enrich the literature on performance assessment using the Balance Scorecard with the Charting The Field method. This study uses article data from 7 journals totaling 24 article with the key word "Balance Scorecard" published in Sinta 2 and Sinta 3 with the research period 2009-2019. This study classifies each sample article into 3 (three) categories, namely the journal group, year of publication, and research method. The results showed that the journal that published the most articles with the topic Balance Scorecard was the Udayana University Accounting E-Journal with 15 articles, the research topic most often used is Consequences with a percentage of 79% of the articles, 2013 was the year with the most number of articles with the theme of Balance Scorecard with 5 articles, and the method most used in research on the Balance Scorecard is the Analytical method uses an quantitative approach with a percentage of 67%.